Compare Second Stage of Labour with or without Epidural Analgesia - Nazneen Hameed, Khairunnisa, Asma Ali Depar, Hina Habib, Safia Abdullah (Pakistan Journal of Medical & Health Sciences, 2022)
Background: Epidural analgesia involves the injection of a local anesthetics agent into spinal cord. Delayed pushing has found association between epidural analgesia, instrumental deliveries and prolongation of second stage of labour. Objective: To compare second stage of labour with or without epidural analgesia at Aga Khan University Hospital. Study Design: Cohort study Setting: The Department of Obstetrics and Gynaecology, Aga Khan University Hospital, Karachi. Duration: From 1st March, 2020 to 1st August, 2020 Material and Methods: Total 80 patients were included and equally divided into group who received epidural analgesia and group who did not get epidural analgesia. Dependent variable was epidural analgesia and Independent variables are labor outcome as prolonged 2nd stage of labour with or without epidural analgesia. Stratification was done. Post stratification chi-square test was applied. P-value ≤0.05 was taken as significant. Results: The mean mother’s age in epidural and non-epidural groups was 29.48±4.38 years and 28.08±4.68 years. Prolonged second stage of labour was observed in 12.5% patients of epidural group and 5% patients of non-epidural group. The results showed significant association of prolonged second stage of labour with exposed and unexposed groups. Conclusion: Our study results showed that, prolonged second stage of labour was observed more among women in epidural group as compared to them women in non-epidural group. Keywords: Second Stage Labour, With or Without Epidural Analgesia